Missão e profissão: caminhos da crítica jornalística - Ventura, Mauro de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This work is dividided into two parts: while Part I seeks to understand the relations of rupture and continuity between the instance of criticism and the field of journalism, the second part studies the European essays of Austrian-Brazilian journalist and literacy critic Otto Karpfen (1900-1978). The two sides are united by the common goal of understanding the paths that open up with journalistic criticism. Thus, it brings to the scope of journalism the discussion about the function of criticism and investigates how the mechanisms of criticism operate and what meaning they acquire in the practice of journalism and cultural criticism. The cases of criticism studied in this work can not be isolated from the modes of organization, circulation and reception of symbolic assets, and are also linked to the concepts of the field of diffusion and instances of legitimation. The second part of this thesis studies Otto Karpfen's essays. This task implies the study of the impact caused by the political and personal ruptures related to the historical and social process lived by the author in Austria during the years of 1930. Thus, the European trajectory of Otto Karpfen and his articles published in the weekly Der Christliche Standestaat and in the magazine Die Erfullung, both in Vienna, are studied, with the purpose of making a systematic study of the European phase of the work of the one that was one of the most important critics and cultural journalists of Brazil

Este trabalho divide-se em duas partes: enquanto a Parte 1 busca compreender as relações de ruptura e continuidade que se estabelecem entre a instância da crítica e o campo do jornalismo, a Parte II dedica-se ao estudo de alguns aspectos e temáticas presentes nos ensaios europeus do jornalista e crítico literário austríaco-brasileiro Otto Karpfen (1900-1978). Ambas as partes estão unidas pelo objetivo comum de compreender os caminhos que se abrem com a crítica de linhagem jornalística. Deste modo, o trazer para o campo do jornalismo a discussão sobre a função da crítica, a Parte I busca investigar como operam os mecanismos de criticabilidade we que sentido adquirem na prática do jornalismo e da crítica cultural. Os casos de crítica estudados no decorrer deste trabalho não podem ser isolados dos modos de organização, circulação e recepção dos bens simbólicos e estão ligados, igualmente, aos conceitos de campo e instâncias de difusão e de legitimação. A Parte II desta tese ocupa-se da compreensão da obra ensaística de Otto Karpfen. Esta tarefa implica o estudo do impacto provocado pelas rupturas políticas e pessoais ligadas ao processo histórico e social vivido pelo autor na Àustria durante os anos de 1930. Assim, são estudados tanto a trajetória europeia de Otto Karpfen, quando seus artigos publicados no semanário Der Christliche Standestaat e na revista Die Erfullung, ambos do Viena, com vistas ao estudo sistemático da fase europeia da obra daquele que foi um dos mais importantes críticos literários e jornalistas culturais do Brasil
Mission and work: paths of journalist criticism
Keywords: Journalistic criticism; Literary criticism; Field of diffusion; Instances of legitimacy; Press and society; Political journalism; Modernity; Austria; National socialism; The jewish question.; Jornalismo; Crítica; Difusão; Autenticidade (Filosofia); Imprensa; Sociedade de massa; Civilização moderna; Nacionalismo